PENINGKATAN KETERAMPILAN KOLABORASI PADA MATA PELAJARAN MATEMATIKA MELALUI MODEL TEAMS GAMES TOURNAMENT DI KELAS V SEKOLAH DASAR - Kusumawati, Indah; Kristin, Firosalia (Universitas Muhammadiyah Tapanuli Selatan, 2023)
This study aims to improve the collaboration skills of students in math lessons by applying cooperative type TGT (Teams Tourism Games) learning with class presentation steps, studying in a team, game, game, group announcements, group announcements. This study is a Research on Class Action held in Mangunsari 02 City Prayers in the class V Semester I of 2023/2024 in two cycles with the number of 16 students where 7 men and 9 women. dikumpukkan data using observation sheets of students’ skills in collaborating. Data was analyzed descriptively by comparing the meaningfulness and learning at the results of students from pre cycles, the I cycle and the cycle II. The results show that peningkatakan collaboration skills by implementing the Teams Tournament learning model in the Mathematics subject were the I cycle from 16 students who exist, there are 7 (44%) students who have met the indicator of collaboration skills, compared to pre-19% of students, while in the II cycle from 169 students who are very able to collaborate. Therefore, the TGT model can improve collaboration skills in the cargo of Mathematics learning.